Peningkatan Produktivitas Petani Kopi Arabika Di Desa Sukorejo, Kabupaten Bondowoso Melalui Aplikasi Teknologi Mesin Huller - Sholeh Avivi; Ayu Puspita Arum; Dwi Erwin Kusbianto; Hasbi Mubarak Suud; Gatot Subroto; Sri Hartatik; Muhammad Ubaidillah (Universitas Mataram, 2026)
Sukorejo Village, Sumber Wringin District, has great potential for coffee plantations, particularly the Arabica Laurina cultivar, which is low in caffeine and highly valuable. This coffee is exported to the Netherlands and collaborates with roasteries in Jakarta. However, farmers face challenges due to the limited availability of huller machines, which hinder the coffee processing workflow. This program aims to provide a specially designed huller machine tailored to the village's production capacity and electricity conditions to improve farmers' efficiency. The methods include a coffee production survey, huller machine design by Agricultural Industrial Engineering experts, field trials, and training for farmers on the benefits of the machine. The provided huller machine is expected to enhance the productivity and economic value of Arabica Laurina coffee, strengthen exports, and reduce farmers' burdens. Evaluation is conducted through machine trials to ensure its effectiveness in removing the parchment and silver skin of the coffee beans.